Adsorption and Desorption Characteristics of Cd(II) Ions onto the Adsorbent Derived from Algae - Shunsuke Aizawa; Ryusei Machida; Yoshimasa Amano; Motoi Machida (Journal of Chemical Engineering of Japan)
In this study, cyanobacterial bloom adsorbents (CBA) were prepared by H2SO4 treatment (sulfonic acid-treated CBA; CBA-S) at 90-95 °C and ZnCl2 activation at 100, 200 and 300 °C (zinc chloride-activated CBA; CBA-Z-100, 200 and 300). Then, practicality and reusability of CBA were examined by researching the adsorption/desorption performance of Cd(II) in batch and column methods. In batch method, the amount of 1st adsorption in CBA-S was highest (0.95 mmol/g) and more than twice CBA-Z series. The amounts of 2nd to 4th adsorption in CBA-S were higher than other three samples. The desorption rates were higher than 90% in 2nd to 4th adsorption. Adsorption capacity (Qm) and affinity (Ke) of CBA-S were 1.98 mmol/g and 8.74 L/mmol in Langmuir equation, respectively. CBA-S has many adsorption sites for Cd(II), and its adsorption power is weak. In column method, the adsorption of CBA-S was 0.705 mmol/g when the initial concentration of Cd(II) was 500 mg/L. After desorption, the amounts of 2nd and 3rd adsorption were 0.708 (100%) and 0.655 (93%) mmol/g, respectively. These results indicate that CBA-S had high adsorption performance and could be used repeatedly as clarified by batch and column experiments.